Can we control the amount of useful nonclassicality in a photon added hypergeometric state?. (19th March 2021) - Malpani, Priya; Thapliyal, Kishore; Pathak, Anirban
Abstract: Non-Gaussianity inducing operations are studied in the recent past from different perspectives. Here, we study the role of photon addition, a non-Gaussianity inducing operation, in the enhancement of nonclassicality in a finite dimensional quantum state, namely hypergeometric state with the help of some quantifiers and measures of nonclassicality. We observed that measures to characterize the quality of single photon source and anticlassicality lead to the similar conclusion, i.e. to obtain the desired quantum features one has to choose all the state parameters such that average photon numbers remains low. Wigner logarithmic negativity of the photon added hypergeometric state and concurrence of the two-mode entangled state generated at the output of a beamsplitter from this state show that nonclassicality can be enhanced by increasing the state parameter and photon number addition but decreasing the dimension of the state. In principle, decreasing the dimension of the state is analogous to holeburning and is thus expected to increase nonclassicality. Further, the variation of Wigner function not only qualitatively illustrates the same features as observed quantitatively through concurrence potential and Wigner logarithimic negativity, but illustrate non-Gaussianity of the quantum state as well.